Conceptual principles of organizational and legal support for the implementation of public-private partnership projects in the housing and communal sphere of Ukraine - Folhina , Tetiana (Theory and Practice of Public Administration, 2019)
One of the important factors of economic growth and sustainable development of Ukraine is the modernization and reformation of one of the most energy-intensive and problematic sectors - housing and communal services of Ukraine. This is quite a difficult task, as housing and communal services are an extensive branch of the economic complex of Ukraine, consuming 44% of all country’s energy resources, there are more than 14,2 thousand specialized enterprises and organizations of different ownership forms, which provide consumers with 40 types of housing and communal services. Almost 35% of the state’s fixed assets are operated in the industry, and about 15% of the working population of the country is employed. The study of existing sources and directions of financing of housing and communal services investments shows a significant under-financing of the industry needs at the expense of budgets of all levels. The share of public funds allocated for the provision of the state program of modernization and energy efficiency of housing and communal services is less than 3% of the total need. At the same time, according to the Ministry of Economic Development and Trade of Ukraine, Ukraine needs about 25 billion of investment to solve this problem. As the world experience shows, partnerships between the state and business are mutually beneficial because: for business - the state creates favorable conditions for its functioning through participation in profitable joint projects; for the state, such a partnership is a way of attracting private capital to finance nationally significant projects. Public-Private Partnership (PPP) policy has been successfully applied in more than 50 countries, and especially in economically highly developed countries such as the United States, the United Kingdom, Germany, France and others. In the period from 2000 to 2015, 1,184 PPP projects were implemented in the EU for a total amount of around € 270 billion. For Ukraine, PPP is a certain alternative to privatization, since it allows the state to keep strategic objects while attracting financing on favorable terms. There is a synergistic effect of applying different approaches to project management: new technologies and high standards of social protection, entrepreneurial principles of doing business and state mechanisms for guaranteeing investment, effective management of state property and increasing the list of services provided to the population. According to data of central and local executive authorities in Ukraine as of 01.07.2019 on the basis of PPP, 186 contracts were concluded, of which only 52 contracts were implemented. One of the main reasons for this situation is the lack of trust in the state as a business partner due to the continuing instability of public finances, the volatility of legislation, high level of corruption, including at the middle management level, which is responsible for the implementation of public-private partnership projects. Therefore, the primary objective is to ensure the legal basis of the partnership by adopting amendments to legislation; creation of a management structure based on a clear division of powers of state authorities to manage this structure; forming a unified approach to the functioning of the PPP environment; increasing the efficiency of the implementation of the state support mechanism in the field of PPP; raising the level of training and qualification of specialists of the executive and local self-government bodies on the application of the mechanism of the said partnership.